Ilmu dan Perubahan Sosial - Fitriyani, Fitriyani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Science is any form of activity process towards a particular condition or situation by using tools, methods, methods and procedures. Then, it will produce new knowledge for humans themselves. Meanwhile, a knowledgeable person means a person who has knowledge, understanding, basics, and has limits to knowledge according to the way he seeks the knowledge he has. So that every human being or society during their life must experience a change, which change for the society that studies it can be an interesting or striking event and can also be something that is not interesting to discuss. Some changes occur very quickly and some are slow, changes in society can relate to social values, social norms and so on. Changes in society have existed since ancient times, but nowadays these changes are happening very quickly, so that in responding to them someone must play a role in fostering and guiding society in navigating existing and future changes. And this change cannot be separated from the role of science which continues to develop in society's life. Therefore, this series of articles will examine science and social change as a science that can provide awareness of the relevance and even integration between science and social change itself.